Pedagogical digitalization and the challenges of distance education: Case of the Higher School of Technology of Agadir - El Bettioui, Rachid (2021)
Digitization represents, in our time, a need for development and competitiveness of the majority of sectors. It constitutes a process for transforming objects, professions, methods and tools into digital code that is more efficient. The higher education sector is no exception to this digital transformation. Digital pedagogy has become one of the most suitable forms of learning for the current generation of higher education students who prefer a training model with smart universities.This article mainly consisted of studying the difficulties of distance learning applied in Morocco during confinement due to COVID-19 to maintain the pedagogical programs of students. An online questionnaire was completed by 487 students from the Higher School of Technology of Agadir of University Ibn Zohr in Morocco. Firstly, the collected data was analyzed using the descriptive statistics. Then, the analytical method of Chi-square Test, using SPSS Statistics. Chi-square Test was conducted to analyze the relationships between the variables in the conceptual model. The results of this research revealed that many students experience serious difficulties using digital education platforms. They don't always sign up for their virtual classes on some distance education platforms like Google Meet and Zoom. These digital pedagogical platforms require higher internet connection fees and a pre-service training and support program.